2016
DOI: 10.1016/j.matbio.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-1 microfibrils influence adult bone marrow hematopoiesis

Abstract: We have recently demonstrated that fibrillin-1 assemblies regulate the fate of skeletal stem cells (aka, mesenchymal stem cells [MSCs]) by modulating TGFβ activity within the microenvironment of adult bone marrow niches. Since MSCs can also influence hematopoietic stem cell (HSC) activities, here we investigated adult hematopoiesis in mice with Cre-mediated inactivation of the fibrillin-1 (Fbn1) gene in the mesenchyme of the forming limbs (Fbn1Prx1−/− mice). Analyses of 3-month-old Fbn1Prx1−/− mice revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…2B). With regard to enhanced bone resorption, dysregulated marrow hematopoiesis in Fbn1 Pr1x −/− mice might also contribute to increasing the number of osteoclasts [46]. A decreased amount of proteolytic fragments of fibrillin-1 that normally restrict osteoclast differentiation through RANKL sequestration and NFATc inhibition might potentially be another stimulator of bone catabolism in Fbn1 Pr1x −/− mice [47].…”
Section: Mfs; Molecular Pathophysiologymentioning
confidence: 99%
“…2B). With regard to enhanced bone resorption, dysregulated marrow hematopoiesis in Fbn1 Pr1x −/− mice might also contribute to increasing the number of osteoclasts [46]. A decreased amount of proteolytic fragments of fibrillin-1 that normally restrict osteoclast differentiation through RANKL sequestration and NFATc inhibition might potentially be another stimulator of bone catabolism in Fbn1 Pr1x −/− mice [47].…”
Section: Mfs; Molecular Pathophysiologymentioning
confidence: 99%
“…Both β3 integrins belong to the subgroup of RGD binding integrins, i.e., integrins recognizing ligands containing an RGD tripeptide sequence. These integrins are among the most promiscuous and bind to a large number of ligands, including extracellular matrix and soluble vascular ligands [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Important ligands for the β3 integrins are given in Table 1 .…”
Section: The Promiscuity Of β3 Integrin Ligand Bindingmentioning
confidence: 99%
“…It was recently shown that fibrillin-1 microfibrils have an important role in bone marrow ECM. Specifically, immunofluorescence was used to localize fibrillin-1 to stem cell niches, and Prx1-Cremediated loss of fibrillin-1 ( Fbn1 Prx −/− ) modified skeletal stem cell fate, erythroid expansion, and HSC maintenance [19,20]. The presence ofMAGP1’smajor binding partner - fibrillin-1 - within the bone marrow provides an ideal docking station for MAGP1 protein in Mfap2 Prx −/− mice.…”
Section: Discussionmentioning
confidence: 99%